Correlation coefficient of agronomic attributes on sweet sorghum [Sorghum bicolor (L.) Moench] - Singh, S.P.; Singh, R.K.; Kumar, S.; Joshi, Y.P.; Singh, Lakhapati (Annals of Agricultural Research, 2016)
Correlation coefficient analysis was carried out to elucidate inter relationship on sweet sorghum among growth parameters (plant height, leaf area index, mid stem diameter; leaf: stem ratio) with yield parameters (stalk, juice, sugar, ethanol, fodder, crude protein content and in vitro dry matter digestible yield). Quality parameters (juice percent, brix percent, juice purity coefficient and sucrose percent) were also correlated to each other and yield parameters (cane yield, sugar yield, juice yield and ethanol yield). Positive correlations were observed between growth, yield and quality parameters.